Ze śmiercią im do twarzy: żywe trupy końca XX wieku - Marcela, Mikołaj (Er(r)go. Teoria - Literatura - Kultura, 2014)
Mikołaj Marcela Death Becomes Them: Living Dead at the End of the 20th Century It seems that the return of the living dead in Robert Zemeckis’s Death Becomes Her (1992) is not the return of repressed death, like in George A. Romero’s films, but rather the return of the repressed of our modern fears: fear of being ugly and fat, and fear of being old. Today, when we are surrounded by beautiful celebrities from television and newspapers, we cannot afford to let our body get out of shape. It appears that to remain human we have to retain our beauty and shape. But even more horryfing seems the threat of growing old. Michel Vovelle points out that the process of growing old appears as one of the most horrible threats for Western civilization. Hidden and repressed it returns in the figure of zombie in Romero’s classic movie series. The “living dead” truly returns to the cinema in 1968 (Night of the Living Dead)—the year in which Jean Amèry issues his essay On Growing Old. From its perspective it becomes obvious that slow and unproductive zombies, “the living dead” which crave only for consumption, represent the senior citizens society that endangers contemporary culture of youth, beauty and health. Simon Clark regards the blood-stained mouth of a zombie as a variation of vagina dentata while Maria Bonaparte perceives it as a symbol of castration and impotence.